2013
DOI: 10.1371/journal.pone.0055995
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Processing and Speech Perception in Noise by Listeners with Auditory Neuropathy

Abstract: AimThe present study evaluated the relation between speech perception in the presence of background noise and temporal processing ability in listeners with Auditory Neuropathy (AN).MethodThe study included two experiments. In the first experiment, temporal resolution of listeners with normal hearing and those with AN was evaluated using measures of temporal modulation transfer function and frequency modulation detection at modulation rates of 2 and 10 Hz. In the second experiment, speech perception in quiet an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…More recently, it has been demonstrated that poor temporal resolution rather than the frequency resolution exerts the major detrimental effects on the FS cue processing for pitch perception for subjects with ANSD . The findings of the present study are in accordance with those of Narne, who demonstrated that fine structure processing was severely degraded in listeners with ANSD, and that the dramatically decreased performance in lexical tone recognition for the listeners with ANSD was due to the abolished ability to process the FS cues. Furthermore, the assessment of temporal modulation detection in listeners with ANSD showed greatly elevated thresholds in the temporal modulation transfer functions (TMTF) and a large individual variability in the TMTF, suggesting that listeners with ANSD may suffer from an abnormal processing of the E cues.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…More recently, it has been demonstrated that poor temporal resolution rather than the frequency resolution exerts the major detrimental effects on the FS cue processing for pitch perception for subjects with ANSD . The findings of the present study are in accordance with those of Narne, who demonstrated that fine structure processing was severely degraded in listeners with ANSD, and that the dramatically decreased performance in lexical tone recognition for the listeners with ANSD was due to the abolished ability to process the FS cues. Furthermore, the assessment of temporal modulation detection in listeners with ANSD showed greatly elevated thresholds in the temporal modulation transfer functions (TMTF) and a large individual variability in the TMTF, suggesting that listeners with ANSD may suffer from an abnormal processing of the E cues.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that the ability to perceive lexical tone in these individuals generally degraded progressively with increasing severity of hearing loss. Nevertheless, there were large individual differences in tone recognition performance, especially for those with mild to moderate hearing loss, as might be expected when assessing any perceptual measures . Note, however, that if we pooled together the data of the two groups of subjects, the correlation between tone recognition performance and PTA 0.5–4 kHz disappeared.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In contrast, listeners with ANSD may have a dramatically impaired ability for processing temporal information (Narne 2013), while their frequency selectivity may be close to normal (Vinay and Moore 2007). To clarify whether it is the deficit in temporal resolution or frequency resolution that may lead to more detrimental effects on FS processing in lexical tone perception, we also measured the frequency resolution using the mean Q 10 dB values of the psychophysical tuning curves (PTCs), and the temporal resolution using the temporal gap detection (TGD) threshold for the SNHL and ANSD subjects.…”
Section: The Frequency Resolution and Temporal Resolutionmentioning
confidence: 99%
“…Auditory neuropathy spectrum disorder (ANSD) is an auditory disorder characterized by dys-synchrony of the auditory nerve firing but normal cochlear amplification function. Several studies have demonstrated that ANSD listeners have a dramatically impaired ability for processing temporal information (Zeng et al 1999;Narne 2013). It is important to assess the ability of lexical tone perception for ANSD listeners and to investigate how they use FS and E cues to perceive lexical tone, as these results may shed light on the effects of frequency resolution and temporal resolution on FS processing in pitch perception.…”
Section: Introductionmentioning
confidence: 99%